Hepatitis A vaccine uptake among men who have sex with men from a time-limited vaccination programme in Melbourne in 2018. (25th July 2019) - Burrell, Sam; Vodstrcil, Lenka A; Fairley, Christopher K; Kilner, Alex; Bradshaw, Catriona S; Chen, Marcus Y; Chow, Eric P F
Abstract : Objectives: In 2017, an outbreak of hepatitis A among gay, bisexual and other men who have sex with men (MSM) was reported in Victoria, Australia. In 2018, the Victorian government implemented a free hepatitis A vaccination programme targeting all Victorian MSM. This study aimed to determine hepatitis A vaccine uptake among MSM in a sexual health clinic in Melbourne. Methods: All MSM attending the Melbourne Sexual Health Centre (MSHC) in 2018 were included. Chart review was performed to determine the proportion of men vaccinated for at least one dose of hepatitis A and to examine why men did not receive the vaccine. Multivariable logistic regression was performed to examine the factors associated with vaccine uptake. Vaccine uptake was defined as receipt of at least one dose of hepatitis A vaccine. Results: Of the 9582 MSM who attended MSHC in 2018, 61.3% (95% CI 60.3% to 62.2%) self-reported already being immune to hepatitis A. Of the 3713 remaining eligible men, 62.7% (95% CI 61.1% to 64.2%) received at least one dose of the hepatitis A vaccine on the day of attendance. Compared with MSM not living with HIV and not taking pre-exposure prophylaxis (PrEP), MSM taking PrEP (adjusted OR 1.28; 95% CI 1.01 to 1.62) were more likely to receive the vaccine. 1386 men (37.3%) did not receive the vaccine and 55.4% were not offered the vaccine by their treating clinician. 300 men (21.6%) were identified as non-immune after serological testing but did not return for vaccination. By the end of 2018, 85.5% of MSHC attendees (8196/9582) were immune to hepatitis A. Conclusion: The critical vaccination threshold for hepatitis A has been estimated at >70%. Continuation of the targeted hepatitis A vaccination programme will improve immunity among the MSM population to prevent ongoing transmission and the likelihood of future outbreaks.